2020
DOI: 10.1007/s00024-020-02489-x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling 2018 Anak Krakatoa Flank Collapse and Tsunami: Effect of Landslide Failure Mechanism and Dynamics on Tsunami Generation

Abstract: The 2018 Anak Krakatoa volcano flank collapse generated a tsunami that impacted the Sunda Strait coastlines. In the absence of a tsunami early warning system, it caused several hundred fatalities. There are ongoing discussions to understand how the failure mechanism of this event affected landslide dynamics and tsunami generation. In this paper, the sensitivity to different failure scenarios on the tsunami generation is investigated through numerical modelling. To this end, the rate of mass release, the landsl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…Heidarzadeh et al (2020a) analyzed tide gauge records of the AKT and proposed a source model for this unique tsunami by applying numerical simulations; the source model proposed by Heidarzadeh et al (2020a) consists of an initial pure-elevation wave with height of 100-150 m and length of 1.5-2.0 km. The numerical modeling of the event by Paris et al (2020) and Zengaffinen et al (2020) further reconfirmed the source model initially proposed by Heidarzadeh et al (2020a). The volume of the sliding mass during the AKT was estimated at 0.2-0.3 km 3 by Ren et al (2020) whereas Heidarzadeh et al (2020a) reported it in the range of 0.175-0.326 km 3 .…”
Section: Introductionsupporting
confidence: 65%
“…Heidarzadeh et al (2020a) analyzed tide gauge records of the AKT and proposed a source model for this unique tsunami by applying numerical simulations; the source model proposed by Heidarzadeh et al (2020a) consists of an initial pure-elevation wave with height of 100-150 m and length of 1.5-2.0 km. The numerical modeling of the event by Paris et al (2020) and Zengaffinen et al (2020) further reconfirmed the source model initially proposed by Heidarzadeh et al (2020a). The volume of the sliding mass during the AKT was estimated at 0.2-0.3 km 3 by Ren et al (2020) whereas Heidarzadeh et al (2020a) reported it in the range of 0.175-0.326 km 3 .…”
Section: Introductionsupporting
confidence: 65%
“…The second failure mechanism proposed is that the flank collapse was one event, with a larger volume than proposed by Williams et al (2019) (Grilli et al, 2019;Zengaffinen et al, 2020). The failure mechanism in this instance may have resulted from the steep gradient of the southwest Anak Krakatau slope, and the growth of significant lava flows in this region.…”
Section: Discussionmentioning
confidence: 85%
“…Paris et al (2020), presents a preliminary model of the volcanic collapse based on coupled granular rheology and coulomb friction. In addition, Zengaffinen et al (2020), modeled the Anak Krakatau flank collapse using a depthaveraged visco-plastic with BingClaw landslide model. From this, the authors were able to reproduce the tsunami elevation amplitudes recorded in the field surveys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the majority of large tsunamis are produced by underwater earthquakes 4 , the latest tsunami event in Indonesia revealed the importance of studying other tsunami sources (such as subaerial, submarine landslide and earthquake-induced landslide). For instance, the flank collapse of Anak Krakatoa on 22 December 2018 generated tsunami and affected certain areas around Java and southern Sumatra, killed 437 people 5 . Field survey reported that this tsunami produced wave run-up more than 85 m at the northern coast of Rakata and 83 m at the southern coast of Sertung 6 .…”
Section: Introductionmentioning
confidence: 99%